2020
DOI: 10.3389/fnagi.2020.00165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Potential Key Circular RNAs in Elderly Patients With Postoperative Cognitive Dysfunction

Abstract: Background: Postoperative cognitive dysfunction (POCD) is one of the severe complications after surgery, inducing low life quality and high mortality, especially in elderly patients. However, the underlying molecular mechanism of POCD remains largely unknown, and the ideal biomarker for clinical diagnosis and prognosis is lacking. Circular RNAs (circRNAs), as a unique class of non-coding RNAs, were characterized by its stability and conservativeness, serving as novel biomarkers in various diseases. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…According to previous studies, ,, profiling of circRNAs was conducted via the following details: (1) total RNA extraction, (2) RNA measurement with NanoDrop, (3) RNA library construction, (4) RNA sequencing (RNA-seq) analysis, (5) FAST-QC and circRbase database, (6) bioinformatic analysis (|log 2 fold change| > 2 and P < 0.05, Miranda and RNA hybrid predicted target genes, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated functions of circRNA, Cytoscape software constructed a circRNA-miRNA-mRNA network), and (7) relative expression using qRT-PCR by the formula 2 –ΔΔ Ct .…”
Section: Differentially Expressed Ncrnas In Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, ,, profiling of circRNAs was conducted via the following details: (1) total RNA extraction, (2) RNA measurement with NanoDrop, (3) RNA library construction, (4) RNA sequencing (RNA-seq) analysis, (5) FAST-QC and circRbase database, (6) bioinformatic analysis (|log 2 fold change| > 2 and P < 0.05, Miranda and RNA hybrid predicted target genes, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicated functions of circRNA, Cytoscape software constructed a circRNA-miRNA-mRNA network), and (7) relative expression using qRT-PCR by the formula 2 –ΔΔ Ct .…”
Section: Differentially Expressed Ncrnas In Subjectsmentioning
confidence: 99%
“…The hsa-circRNA-089763 may bind to miR-7111-3p, miR-6769b-3p, and miR-670-3p, all of which may regulate the IGFBP5 gene . In elderly patients with POCD undergoing elective cardiac surgery, hsa_circRNA_001145 potentially functions with miR-1226-5p as a sponge on the ITSN1 gene; hsa_circRNA_101138-hsa-miR-107-NEDD9 was in the network . A list of roles of ncRNA axes in POCD is presented in Table .…”
Section: Differentially Expressed Ncrnas In Subjectsmentioning
confidence: 99%
“…In recent years, studies on the regulation of gene transcription in POD have increased. Gao et al (2020) analyzed the differential expression profile of circRNAs in the blood of POD patients and found that circRNAs are involved in the regulation of development processes, cell adhesion and nervous system development and are enriched in the MAPK signaling pathway and RAS signaling pathway. Wu W. et al (2021) analyzed the expression of circRNAs, miRNAs and mRNAs in the prefrontal cortex by NGS sequencing technology and believed that neuroinflammation was the main pathological mechanism of POD.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small noncoding RNAs that can bind to the 3'-untranslated region (3'-UTR) of the transcript of their homologous target genes, thereby regulating their expression [9]. Extensive studies have confirmed a broad association between miRNAs and anesthesia-related cognitive impairment [9][10][11]; miRNAs, such as miR-665, miR-572, and miR-181, have been reported to affect POCD progression, suggesting that these miRNAs could serve as promising therapeutic targets for treating POCD [12].…”
Section: Introductionmentioning
confidence: 99%